2001
DOI: 10.1103/physreva.63.045401
|View full text |Cite
|
Sign up to set email alerts
|

Propensity of molecules to spatially align in intense light fields

Abstract: The propensity of molecules to spatially align along the polarization vector of intense, pulsed light fields is related to readily-accessible parameters (molecular polarizabilities, moment of inertia, peak intensity of the light and its pulse duration). Predictions can now be made of which molecules can be spatially aligned, and under what circumstances, upon irradiation by intense light. Accounting for both enhanced ionization and hyperpolarizability, it is shown that all molecules can be aligned, even those … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This component has no analog in measurements with atomic clusters and we ascribe it to the ionization signal from unclustered N 2 molecules that are present in the supersonic beam. The asymmetry that is observed is attributed to spatial alignment of the molecular axis along the laser polarization vector, a feature of laser-molecule interactions that has been well studied [2,14]. We note that N 2 has a very low value of the empirical constant in the Hagena parameter [13], indicating that this molecule has low propensity for clustering; thus we observe a component of unclustered N 2 molecules that also emerges from the skimmer.…”
mentioning
confidence: 55%
“…This component has no analog in measurements with atomic clusters and we ascribe it to the ionization signal from unclustered N 2 molecules that are present in the supersonic beam. The asymmetry that is observed is attributed to spatial alignment of the molecular axis along the laser polarization vector, a feature of laser-molecule interactions that has been well studied [2,14]. We note that N 2 has a very low value of the empirical constant in the Hagena parameter [13], indicating that this molecule has low propensity for clustering; thus we observe a component of unclustered N 2 molecules that also emerges from the skimmer.…”
mentioning
confidence: 55%
“…In the case of I 2 , they concluded that dynamic alignment was inefficient under the conditions accessed in the experiment [13]. Similarly, the dependence of the observed alignment on the laser intensity was also used by Banerjee et al to distinguish dynamic from geometric alignment [17].…”
Section: Introductionmentioning
confidence: 90%
“…Here the central barrier between the two atoms has risen to such an extent that it strongly inhibits adiabatic adjustment to the laser field, and localization of the outer electron on one of the two atoms occurs. To simulate the results of our experiment we have extended this model (similar to the work in [17]) by including the dynamic rotation of the molecule induced by the laser field [25]. Our model calculations are presented only briefly in this paper and are the subject of a companion paper published separately [19].…”
Section: The Extended Coulomb Explosion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…θ , related to the components of second-hyperpolarizability tensor ijkl γ (these higher-order perturbations are apparently more important in the case of asymmetric molecules where first hyperpolarizability ikl β is engaged). [28][29][30][31][32][33] However, when the laser electric field becomes so strong that 0 ~E μ Δ  , the perturbation series for the electronic response does not converge any more, and thus incorporating higherorder perturbations in…”
Section:  | |mentioning
confidence: 99%